Agroforestry in bean research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
CIAT scientists working on the Great Lakes Bean Project in Rwanda have developed an interest in agroforestry - the production system where woody perennials are grown on the same land as agricultural crops. At present 40% of the beans produced in...